1998
DOI: 10.1159/000015151
|View full text |Cite
|
Sign up to set email alerts
|

A satellite DNA of the Sparidae family (Pisces, Perciformes) associated with telomeric sequences

Abstract: This paper reports on the isolation and localization of the subtelomeric DraI satellite DNA in the Sparidae family. Gene cloning determined that the DraI satellite DNA is present in only 3 species (Pagrus pagrus, P. auriga, and Pagellus erythrinus) of the 10 Sparidae species analyzed. The results were confirmed by PCR amplification. This satellite DNA is located in a subtelomeric position in all 48 acrocentric chromosomes of these species. However, interstitial loci are also observed. Sequence analysis of mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 40 publications
1
41
0
Order By: Relevance
“…The reduction of the chromosome number from 2n = 48, which is supposed to be ancestral for teleost fish (Brum and Galetti, 1997), to 2n = 44 in Nile tilapia (Oreochromis niloticus) by fusion of three chromosomes, left two interstitial telomeric sites on the two largest chromosomes in its karyotype (Chew et al, 2002). On the other hand, in some vertebrate species, the (TTAGGG) n sequence has been reported as a component of the satellite DNA (Adegoke et al, 1993) which can be located in subtelomeric as well as interstitial positions in chromosomes (Garrido-Ramos et al, 1998). Finally, it is important to note that guanine-rich elements such as variable number of tandem repeats (VNTR) or NOR-regions (Ashley and Ward, 1993) are listed besides telomeres and centromeres as elements involved in jumping translocation processes followed by ITS formation.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of the chromosome number from 2n = 48, which is supposed to be ancestral for teleost fish (Brum and Galetti, 1997), to 2n = 44 in Nile tilapia (Oreochromis niloticus) by fusion of three chromosomes, left two interstitial telomeric sites on the two largest chromosomes in its karyotype (Chew et al, 2002). On the other hand, in some vertebrate species, the (TTAGGG) n sequence has been reported as a component of the satellite DNA (Adegoke et al, 1993) which can be located in subtelomeric as well as interstitial positions in chromosomes (Garrido-Ramos et al, 1998). Finally, it is important to note that guanine-rich elements such as variable number of tandem repeats (VNTR) or NOR-regions (Ashley and Ward, 1993) are listed besides telomeres and centromeres as elements involved in jumping translocation processes followed by ITS formation.…”
Section: Discussionmentioning
confidence: 99%
“…This phylogeny of the Sparidae family is also supported by previous data obtained from the analysis of another satellite DNA, the DraI family, found within the genome of some sparids. While EcoRI is a satellite DNA family conserved in every sparid species, the DraI satellite DNA is restricted to the genome of the species of Pagrus and Pagellus, and it is absent from the genome of the rest of species belonging to a different clade (Garrido-Ramos et al, 1995a, 1998. It is also noteworthy that the species belonging to one of the lineages (Pagrus and Pagellus) are the last species maintaining the ancestral karyotype of fish composed of 48 acrocentric chromosomes (Ohno, 1974), while the species of the other lineage have derived karyotypes (Garrido-Ramos, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is still unknown how the telomeric DNA sequences were inserted into the interstitial positions and amplified, the repair of the DNA Double Strand Breaks with the telomerase should be taken into consideration (Nergadze et al, 2004(Nergadze et al, , 2007. Previously, several authors suggested that telomeric or telomeric like DNA sequences were components of the satellite DNA in some vertebrates (Garrido-Ramos et al, 1998). In other species, telomeric DNA sequences are scattered along the NORs (Nucleolus Organizer Region) DNA sequences (see chapter 4.4).…”
Section: Non-telomeric Ttaggg Sequences As Components Of the Satellitmentioning
confidence: 99%
“…It is possible that telomeric DNA sequences were not the only component of the ITS region. Internally inserted short telomeric repeats are frequently flanked by the repetitive or transposable elements and undergo amplification process leading to elongation/expansion of the chromatic region built with different DNA sequences including telomeric repeats (Garrido-Ramos et al, 1998).…”
Section: Itss and Minor Rearrangements -A Salvelinus Fish Casementioning
confidence: 99%